Mate Preferense : A Scoping Review - Asyifa Atira Ariamukti; Sari, Yunita (UNISBA Press, 2024)
Abstract. This scoping review navigates the landscape of mate preferences in young adulthood, a developmental phase from late adolescence to mid-twenties. Based on studies from 2013 to 2023, key predictors of mate choice include religion, where shared beliefs, deep understanding and family background influence choice. There were gender-specific variations in assessing physical attractiveness, with men prioritizing it more than women. Character traits such as altruism and responsibility are important to both genders. Economic stability and educational status are important considerations, with women often prioritizing financial support and men emphasizing physical attractiveness. External influences include cultural norms, media exposure and the impact of COVID-19. While the current study highlights preferences from these different sides, future research could explore the dynamic process of preference formation and study different types of relationships. Abstrak. Tinjauan cakupan ini menavigasi tinjauan lanskap preferensi pasangan pada masa dewasa muda, sebuah fase perkembangan dari akhir masa remaja hingga pertengahan usia dua puluhan. Berdasarkan studi dari tahun 2013 hingga 2023, prediktor utama dalam pemilihan pasangan meliputi agama, di mana keyakinan yang sama, pemahaman yang mendalam, dan latar belakang keluarga memengaruhi pilihan. Terdapat variasi spesifik gender dalam menilai daya tarik fisik, dengan pria lebih memprioritaskan hal tersebut dibandingkan wanita. Sifat-sifat karakter seperti altruisme dan tanggung jawab sangat penting bagi kedua jenis kelamin. Stabilitas ekonomi dan status pendidikan adalah pertimbangan penting, dengan wanita sering memprioritaskan dukungan finansial dan pria menekankan daya tarik fisik. Pengaruh eksternal mencakup norma budaya, paparan media, dan dampak COVID-19. Meskipun penelitian saat ini menyoroti preferensi dari berbagai sisi ini, penelitian di masa depan dapat mengeksplorasi proses dinamis pembentukan preferensi dan mempelajari berbagai jenis hubungan.